25th ANNIVERSARY OF CLONING BY SOMATIC CELL NUCLEAR TRANSFER: Generation of genetically engineered livestock using somatic cell nuclear transfer. Issue 1 (16th June 2021) - Polejaeva, Irina A
Abstract : Genetic engineering (GE) of livestock initially has been accomplished primarily using pronuclear microinjection into zygotes (1985–1996). The applications of the technology were limited due to low integration efficiency, aberrant transgene expression resulting from random integration and the presence of genetic mosaicism in transgenic founder animals. Despite enormous efforts to established embryonic stem cells (ESCs) for domestic species, the ESC GE technology does not exist for livestock. Development of somatic cell nuclear transfer (SCNT) has bypassed the need in livestock ESCs and revolutionized the field of livestock transgenesis by offering the first cell-based platform for precise genetic manipulation in farm animals. For nearly two decades since the birth of Dolly (1996–2013), SCNT was the only method used for the generation of knockout and knockin livestock. Arrival of CRISPRS/Cas9 system, a new generation of gene-editing technology, gave us an ability to introduce precise genome modifications easily and efficiently. This technological advancement accelerated production of GE livestock by SCNT and reinstated zygote micromanipulation as an important GE approach. The primary advantage of the SCNT technology is the ability to confirm in vitro that the desired genetic modification is present in the somatic cells prior to animal production. The edited cells could also be tested for potential off-target mutations. Additionally, this method eliminates the risk of genetic mosaicism frequently observed following zygote micromanipulation. Despite its low efficiency, SCNT is a well-established procedure in numerous laboratories around the world and will continue to play an important role in the GE livestock field.